THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION: A LITERATURE REVIEW - Budi Susanto; Martinus Tukiran; Wahyu Wiguna (International Journal of Economy, Education and Entrepreneurship, 2023)
Leadership is one of the most important factors determining whether or not an organization successfully meets its goals and objectives. There are numerous styles of leadership, including transactional leadership, transformational leadership, and servant leadership, among others. The transactional style is based on a transactional relationship between the leader and the follower, where rewards and punishments motivate followers. Transformational leadership involves inspiring and empowering followers to achieve their full potential. Servant leadership prioritizes meeting the needs of followers, which can lead to better performance and employee satisfaction. The purpose of this study was to investigate the relationship between transformational leadership and human resource development as it relates to job satisfaction, as well as how levels of job satisfaction ultimately influence levels of job engagement among employees. The literature study method this research utilizes involves selecting relevant topics and keywords related to the research question and then using these to search for relevant journals and literature to inform the study. The findings from the three studies show that transformational leadership has a positive and significant impact on job satisfaction and engagement and that human resource development plays a crucial role in improving employee satisfaction and engagement. Characteristics such as individualized consideration, inspirational motivation, and intellectual stimulation have been as having a positive impact on job satisfaction. Leaders who develop transformational leadership skills and provide opportunities for human resource development can improve employee satisfaction and engagement.